CURCUMA XANTHORRHIZA ROXB. IN DIGESTIVE HEALTH MANAGEMENT: A SYSTEMATIC REVIEW OF PHARMACOLOGICAL AND ETHNOMEDICAL EVIDENCE - Gladis Avika; Abdullah, Dessy (Yayasan Nusantara Hasana Berdikari, 2025)
Curcuma xanthorrhiza Roxb. (commonly known as Temulawak) is a traditional Indonesian medicinal plant widely used for managing digestive disorders. This systematic review aims to critically evaluate the pharmacological mechanisms, clinical relevance, and ethnomedicinal applications of Curcuma xanthorrhiza in digestive health. Literature was obtained from PubMed, ScienceDirect, Scopus, Google Scholar, and Garuda from 2013 to 2023, using keywords including